Family Ties and Young Fathers' Engagement in Cape Town, South Africa. Issue 2 (April 2015) - Clark, Shelley; Cotton, Cassandra; Marteleto, Letícia J.
<x xml:space="preserve">Abstract</x> Young South African fathers are often engaged in their children's lives even if they do not live together. Using longitudinal data on children (n = 1, 209) from the Cape Town area, the authors show that although only 26% of young fathers live with their children, 66% of nonresidential fathers maintain regular contact, and 61% provide financial support. The father–child relationship, however, is embedded in broader family ties. The type of father–mother relationship is strongly associated with whether fathers coreside with their children but not with fathers' contact with nonresidential children. Close mother and maternal grandmother bonds reduce the likelihood that fathers live with their children, whereas close ties between fathers and paternal grandmothers increase the chance that fathers visit nonresidential children. Family ties do not affect fathers' financial contributions, which are driven by men's current economic situation. These findings illustrate that father–child relationships are best understood in the context of interacting family systems.